DAMPAK KOPERASI UNIT DESA (KUD) TERHADAP KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DESA KABUN KECAMATAN KABUN KABUPATEN ROKAN HULU - Nur Elyna Dewi; Yonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Cooperative aims to build and develop the potential of the economy or the ability of members in particular and society in general to improve the economic and social welfare. To that end, the existence of the village cooperative must participate actively in efforts to enhance the quality of human life and society, strengthen the economy of rural communities as the basis for the strength and resilience of the national economy, and strive to realize and develop the economy of which is a joint effort based on the principle of family.In this study, refers to a theory Flassy (2009) as an instrument of research include parameters that become social resources KUD cooperatives or social capital that became Bumi Asih enter and influence on senuah empowerment of cooperatives, including public trust, social norms, and social networks. The study uses a quantitative approach with the research method used descriptive in explaining the results. Then the instrument of data collection include observation, questionnaires, study the documentation relating to the purpose of research.The results showed that the Village Unit Cooperatives (KUD) Bumi Asih Village Kabun can be perceived positively by members of the KUD Bumi Asih. This is due to social capital or social resources strongly held, either in the form of trust fellow cooperative members and officials as well as community, social norms, and social interaction and social networks are intertwined, so that the effect of the presence of KUD Earth supporting conditions of social and economic life of society , namely with established social relationships and the creation of jobs for rural communities Kabun in line with the development of the business units within the KUD Bumi Asih.Keywords: Village Unit Cooperatives, Social Capital, Trust (Trust), Social Norms, Social Networking.